Construct Validity of the Autism Impact Measure (AIM). - Mazurek, Micah O.; Carlson, Coleen; Baker-Ericzén, Mary; Butter, Eric; Norris, Megan; Kanne, Stephen (Journal of Autism & Developmental Disorders, 2020)
The Autism Impact Measure (AIM) was designed to track incremental change in frequency and impact of core ASD symptoms. The current study examined the structural and convergent validity of the AIM in a large sample of children with ASD. The results of a series of exploratory and confirmatory factor analyses yielded a final model with five theoretically and empirically meaningful subdomains: Repetitive Behavior, Atypical Behavior, Communication, Social Reciprocity, and Peer Interaction. The final model showed very good fit both overall and for each of the five factors, indicating excellent structural validity. AIM subdomain scores were significantly correlated with measures of similar constructs across all five domains. The results provide further support for the psychometric properties of the AIM.